2023
DOI: 10.21037/tp-22-261
|View full text |Cite
|
Sign up to set email alerts
|

ADA2 deficiency (DADA2) misdiagnosed as systemic onset juvenile idiopathic arthritis in a child carrying a novel compound heterozygous ADA2 mutation: a case report

Abstract: Background: The deficiency of adenosine deaminase 2 (DADA2) is caused by an autosomal recessive bi-allelic loss-of-function mutation in the adenosine deaminase 2 (ADA2) gene. DADA2 is a monogenic inherited autoinflammatory disorder characterized by early-onset vasculopathy for which the symptoms range from skin lesions to very severe multiorgan involvement, including life-threatening ischemia and/or hemorrhagic strokes. Owing to the diversity of clinical presentation and the absence of suggestive features, dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…it improves the overall clinical manifestations, control fever episodes and vasculopathy, and prevent strokes in patients with ADA2 deficiency syndrome. Although steroids and other immunosuppressive drugs can be used, they are thought not to prevent strokes 14 . In this case, the disease was well controlled on Adalimumab.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…it improves the overall clinical manifestations, control fever episodes and vasculopathy, and prevent strokes in patients with ADA2 deficiency syndrome. Although steroids and other immunosuppressive drugs can be used, they are thought not to prevent strokes 14 . In this case, the disease was well controlled on Adalimumab.…”
Section: Clinical Discussionmentioning
confidence: 99%
“…Patients with DADA2 may present with a range of clinical phenotypes, including recurrent fever, livedo racemosa, ischemic strokes, and hematological abnormalities (Caorsi et al, 2017; Li et al, 2023; Navon Elkan et al, 2014; Zhou et al, 2014). The wide range of disease phenotypes can cause patients to be easily misdiagnosed (Springer et al, 2018; Yin et al, 2023). A recent study estimated a DADA2 prevalence of 1 in 222,164 individuals worldwide, and more than 30,000 DADA2 cases are predicted among the world's population of 7.7 billion (Jee et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study published on Translational Paediatrics , Yin and colleagues ( 15 ) reported a 3-year-old boy with DADA2 who initially presented with nonspecific clinical manifestations including recurrent fever, mildly enlarged lymph nodes, and elevated acute phase reactants, with an initial diagnosis of systemic onset juvenile idiopathic arthritis. The key events leading to a re-evaluation of the initial diagnosis were the presence of intractable hypertension and gastrointestinal complications suspicious for underlying vasculopathy, and an unsustained response to immunosuppressive treatments.…”
mentioning
confidence: 99%
“…Study of Yin et al , which was published on Translational Paediatrics , identified a novel compound heterozygous mutation in ADA2 gene ( 15 ), c.737 G>C (p. Arg246Thr) located in exon 3 and c.827 T>C (p.Phe276Ser) located in exon 4. Their experimental data revealed ADA2 enzyme activity was almost completely lost in this patient.…”
mentioning
confidence: 99%